Evaluation Of Structural Pounding Between Adjacent Buildings Subjected To Repeated Ground Motions - Miari, Mahmoud Ali (2017)
The current codes still have some drawbacks, where the following two basic phenomena are not taken into account: the first is structural pounding (collapse between the structures) which occurs if the gap between the structures is insufficient; and the second phenomenon is the repeated earthquakes, where there is no information in the codes related to it. This research investigates the structural performance (peak ground acceleration (PGA), drift, plastic hinges, and interstorey drift) of adjacent buildings experiencing structural pounding under the effect of moderate repeated ground motions using incremental dynamic analysis (IDA) and then develops the fragility curves for adjacent buildings based on different performance levels. For this purpose, nine models have been analyzed. Each model consists of two frames. The buildings are divided into 3 combinations: (1) two regular frames, (2) one regular frame and one irregular frame and (3) two irregular frames. The gap (space between the structures) is divided into 3 gaps: 1 mm, 10 cm, and 1 m for each combination. Thus, there are 3 combinations and 3 gaps for each combination which means a total of 9 models. Results of analysis prove that the damage of the structure is directly proportional to the intensity of the ground motion and the irregularity of the structure; whereas it is inversely proportional to the gap between the structures. Hence, 1 m is the best spacing to be used in areas that experience repeated earthquakes to avoid structural pounding in contrast with 10 cm and 1 mm. Also, the main damage of the frames is concentrated in the beams. For regular frames, the damage is concentrated in the bottom storeys, while the damage for irregular frames is concentrated at both bottom and top storeys. Therefore, in areas that experience repeated earthquakes, more stiffness should be given to the beams. In this case, the additional stiffness is recommended for both buildings. The location of the additional stiffness should be in the beams that corresponds to the height of the short building, the immediate above and the below beams, respectively. With respect to the columns, the damage is concentrated in the ground floor. For that, additional stiffness should be added to the columns in the bottom storeys, especially in the ground floor.